Goodwood project - Goh, Fong Lin (2008)
Our team, U.niq, collaborates with Goodwood Florist to embark on a brand-building campaign with several creative strategies recommended by us. From our literature review, we realized the importance of a strong brand. Therefore, a consistent theme, “refresh.reborn.recreate” is being used throughout the campaign. We implemented several research methods to achieve a clear understanding of the management, operations and future plans of Goodwood Florist. After gaining a better understanding of the company and its consumers, we feel that it is necessary for Goodwood Florist to enhance its image, reposition and strategize itself so as to target new potential consumers. With these objectives, Goodwood Florist will be able to gain an edge over its competitors in the industry. In order to achieve these objectives, our campaign targets to re-brand the company using a subtle approach. Two events were proposed to publicize the new identity of Goodwood Florist.